Effectiveness of single shot spinal analgesia with 0.2% ropivacaine in comparison to 0.2% levobupivacaine for labour analgesia - Kour, Gunmeet; Sharma, Shivani; Singh, Gurbir (International Journal of Research in Medical Sciences, 2024)
Background: Labour pain results in a maternal stress response that is not beneficial for the fetus or mother. Spinal analgesia may be a valuable alternative for relieving labour pain. Ropivacaine and levobupivacaine are the drugs commonly used in spinal analgesia. Objectives were to study the efficacy of single-shot spinal analgesia in labour regarding the onset, quality and duration of analgesia, motor blockade, and labour outcome by either ropivacaine or levobupivacaine. Methods: A prospective observational study conducted in SKIMS, Srinagar which included 60 pregnant women who had received labour analgesia. The patients were divided into two groups. In group I, patients received 1 ml of heavy ropivacaine (0.5%) and in group II patients received 1 ml of heavy levobupivacaine (0.5%). Parameters recorded and assessed were the time of onset of analgesia, duration of epidural analgesia, duration of the first and second and total duration of labour, mode of delivery, fetal heart rate, APGAR scores of the newborn, patient complaints after spinal anaesthesia and mean arterial pressure (MAP), heart rate, visual analogue pain scale (VAS) of the subjects. Results: The two groups showed no statistical difference with respect to different parameters like age, weight, height, gestational age, body mass index (BMI) and cervical dilation before the block. There was statistically significant difference with respect to the time of onset and duration of analgesia, in two groups. No significant difference was seen, in terms of VAS scores across different time periods. Conclusions: There was comparable efficacy in terms of analgesic characteristics in both the groups, but levobupivacaine has a longer duration of analgesia, which is helpful for the effective functioning of labour and patient’s satisfaction.